Improvement of the results of artificial insemination by synchronization of estrus and ovulation for beef cattle treated with GnRH and PGF2 - Dung, Bui Van; Xuan, Chu Thi; Hue, Le Thi; Ty, Le Van (Academia Journal of Biology, 2012)
The aim of this study was to compare the application of the protocol induced synchronization of estrus in two groups of local cattle with and without CL before the treatment GnRH and PGF2α. All cows were injected randomly 100 mg GnRH i.m at any day of the cycle and 2 ml prosolvin (15 mg luprostiol) 7 days after GnRH. From 24h to 72h after the treatment, detected estrus carefully and then carried out artificial insemination (AI) for all estrus cows. The injection of GnRH made 14/37 (37.8%) cows with CL and 19/98 (19.4%) cows without CL to be in heat. The total rate of pregnant cows evaluated by rectal palpation 2.5 months after AI was 15/33 (45.5%). The cows in heat after the complete treatment GnRH-PGF2α were 21/23 (91.3%) for cows with CL and 49/79 (62.0%) for cows without CL. Cows in heat became pregnant after AI were almost the same as it was in case of natural estrus (81.0% and 69.4% respectively). Therefore, the total conception rate was 66/103 (64.1%) for the cows in heat and 66/135 (49.0%) for all cows treated. Cows became in heat after GnRH-PGF2¸ distributed mainly in interval of time from 48h to 72h (90.0%) after PGF2α injection. Thus, there is a need to detect estrus carefully in this period of time and AI was made in the rule AM/PM can be applicable for the field conduction in Dien Bien province